2019
DOI: 10.1109/tfuzz.2018.2866967
|View full text |Cite
|
Sign up to set email alerts
|

A Metahierarchical Rule Decision System to Design Robust Fuzzy Classifiers Based on Data Complexity

Abstract: There is a wide variety of studies that propose different classifiers to solve a large amount of problems in distinct classification scenarios. The No Free Lunch theorem states that if we use a big enough set of varied problems, all classifiers would be equivalent in performance. From another point of view, the performance of the classifiers is dependant of the scope and properties of the datasets. In this sense, new proposals on the topic often focus on a given context, aiming at improving the related state-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Lines 4 and 7 show that the transformers with equipment model numbers 6 and 8 are prone to oil seepage/leakage. Similarly, during the excavation process, it was found that almost every type of transformer had more or less oil seepage/leakage [23]. The analysis of strong association rules is shown in Table 6.…”
Section: Analysis Of Strong Association Rulementioning
confidence: 97%
See 1 more Smart Citation
“…Lines 4 and 7 show that the transformers with equipment model numbers 6 and 8 are prone to oil seepage/leakage. Similarly, during the excavation process, it was found that almost every type of transformer had more or less oil seepage/leakage [23]. The analysis of strong association rules is shown in Table 6.…”
Section: Analysis Of Strong Association Rulementioning
confidence: 97%
“…The location is divided into 14 categories according to the source administrative region of the incomplete data of the current analysis of power equipment, which are A7_1-A7_14. The final index nature is divided into 3 categories according to the Classification Standard for Primary Power Transmission and Transformation Equipment [23]. The standardization numbers are A8_1-A8_3, respectively, as shown in Table 3.…”
Section: Association Rules Of Incomplete Data In Power System Based O...mentioning
confidence: 99%
“…In the history of active suspension control applications, many approaches have been studied by researchers to improve comfort and ride handling (Ding et al, 2020; Li et al, 2020; Liu et al, 2019; Konoiko et al, 2019; Talib and Darus 2017; Vahedi and Jamali 2021). As a result of the conflicting nature of performance requirements such as comfort, handling, and suspension displacement, a variety of control strategies such as linear quadratic regulator (LQR) (Sam et al, 2000), adaptive sliding control (Chen and Huang 2005), H∞ and robust H ∞ control (Du and Zhang 2007), sliding mode control (SMC) (Akbari et al, 2010), FL (Cózar et al, 2019; Ejegwa et al, 2021; Elbab et al, 2009; Xu et al, 2021), preview control (Oraby et al, 2007), proportional integral (PI) control (Yildiz and Kopmaz 2017), optimal control (Marzbanrad et al, 2002, 2003), and neural network methods (Al-Holou et al, 2002) have been studied to handle with the trade-off performance criteria for active suspension control. Nonetheless, by their nature, some of these methods are resource-intensive and may under-perform in unfamiliar conditions.…”
Section: Controller Designmentioning
confidence: 99%
“…Using exact classification techniques developed [9], Access, querying, mining, and information retrieval problems are lessened. Elaggoune et al [10] used neural learning to categorize data according to the attributes connected to it. Similar to this suggestion, classification is modified using batch processing devices and distributed systems to address the problems with excessive resource consumption.…”
Section: Introductionmentioning
confidence: 99%